The effects of demand-resource relationship on work-family conflict under Chinese culture: a cross-sectional study - Li, Tianjiao; Helian, Zhiwei; Hu, Ling; Ma, Mengyuan (Frontiers in Psychology, 2024)
Chinese work and lifestyle are undergoing dramatic changes caused by constantly changing technology and new policies. The demand-resource dynamic relationship, which leads to work-family conflict (WFC), has become increasingly complicated. However, very little is known about the combined effects of different factors from work and family spheres on WFC. This study aims to explore (1) the discrepancy between fit and misfit, (2) the discrepancy of the different degrees of fit, and (3) the discrepancy of the different degrees of misfit from two perspectives: work demand-family resource and work resource-family demand. Data were collected from 745 individuals in China and analyzed using polynomial regression and response surface. The results demonstrate that individuals having low work demand–high family resources experience the lowest WFC, and the fit between work demands and family resources impacts the conflict in a U way. Similarly, high work resource–low family demand results in the lowest WFC; however, the fit between work resources and family demands has negative effects on the conflict. This study took factors from both family and work domains into consideration and explored the effect of their interaction on WFC. By examining the dynamic relationship between demands and resources, adjustments can be made in both domains simultaneously, providing more flexible guidance for management practices that reduce WFC.